2017
DOI: 10.1016/j.bjid.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella species pathogenic for humans infect pets, free-ranging wild mammals and their ectoparasites in the Caatinga biome, Northeastern Brazil: a serological and molecular study

Abstract: This study verified the occurrence of Bartonella spp. in dogs, cats, wild mammals and their ectoparasites in Petrolina and Lagoa Grande Counties, Pernambuco, located in a semi-arid region in Northeastern Brazil. Anti-Bartonella spp. antibodies were detected by indirect immunofluorescence assay (IFA) in 24.8% of dogs (27/109) and in 15% of cats (6/40). Bartonella sp. DNA was identified by PCR performed on DNA extracted from blood and ectoparasites using primers targeting Bartonella sp. gltA and ribC genes in 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
2
22
1
4
Order By: Relevance
“…The found occurrence of Bartonella spp. among wild rodents sampled in the present study was higher (31.8%) than that found among synanthropic rodents (19.2%) in the city of Salvador, state of Bahia, northeastern Brazil [4] and in wild rodents (0%) sampled in the semi-arid region of Pernambuco [6], northeastern Brazil, but similar to that found in a previous recent study involving wild rodents (34.4%) sampled in southern Pantanal [7]. However, the occurrence of Bartonella infection among wild rodents in Pantanal biome in the present study was lower than that found in wild rodents (42.8%) in peri-urban areas from the same state where the present study was performed [5].…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…The found occurrence of Bartonella spp. among wild rodents sampled in the present study was higher (31.8%) than that found among synanthropic rodents (19.2%) in the city of Salvador, state of Bahia, northeastern Brazil [4] and in wild rodents (0%) sampled in the semi-arid region of Pernambuco [6], northeastern Brazil, but similar to that found in a previous recent study involving wild rodents (34.4%) sampled in southern Pantanal [7]. However, the occurrence of Bartonella infection among wild rodents in Pantanal biome in the present study was lower than that found in wild rodents (42.8%) in peri-urban areas from the same state where the present study was performed [5].…”
Section: Discussioncontrasting
confidence: 70%
“…Indeed, fleas are also considered important reservoirs for Bartonella [39]. Recently, B. clarridgeiae and B. henselae were detected in Ctenocephalides felis felis fleas collected from cats in the semi-arid region of Pernambuco, Brazil [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the circulation of the agent has been demonstrated in humans, cats, dogs and wild animals using serological and molecular techniques, but only a few ticks were tested for this pathogen and all were shown to be negative for the presence of DNA of Bartonella spp. (Fontalvo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A high Bartonella prevalence was detected in this study, compared to most other Bartonella sp. cat prevalence studies reported from Brazil (Table 2) (5,6,8,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Discrepancy among studies may be related to differences in the analytical sensitivity of laboratory diagnostic methods used among different studies.…”
Section: Discussionmentioning
confidence: 99%